Sheep milk quality in the Basque Country community and Navarre from 1996 to 1998 - Legarra A. (Production systems and product quality in sheep and goats, 2001)
A data set of 43,536 tank milk samples representing the population of the Latxa breed in Navarre and the Basque Country community was analysed. Monthly averages showed a typical increasing tendency for fat and protein contents and somatic cell count throughout the lactation and no variation in total bacterial count was found. As for hygienic quality, it was either good or bad, with few intermediate cases, showing that this can be a feasible objective. Different mean values were calculated by regions and seasons, showing that milk contents were slightly higher in early lambing systems (winter). No clear tendencies were observed for somatic cell and total bacteria counts, but differences existed between regions.
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)